Green Logistics in Practice, A Qualitative Study of Port Sustainability in Eastern Indonesia - Wasil, Mohammad; Jakfar; Firdaus, Muhammad Iqbal (Logistica : Journal of Logistic and Transportation, 2024)
This study examines the implementation of green logistics strategies in freight transportation at Soekarno Hatta Port, Makassar. Data were collected over three months (July–September 2024) through in-depth interviews with 15 informants, participatory observation, and document analysis. Informants represented port authorities, logistics operators, truck drivers, government officials, and academics. Findings show that 9 of 15 informants at managerial level demonstrated high awareness of green logistics, while most operational staff (6 drivers and dock operators) had limited knowledge. Existing initiatives include optimized truck scheduling to reduce idle time and partial electrification of cargo handling equipment. However, barriers such as the lack of electric vehicle infrastructure, absence of regional regulations, and limited sustainability training hinder broader adoption. The study recommends integrating digital emission monitoring, introducing regional fiscal incentives, and developing targeted training programs. By addressing these gaps, Soekarno Hatta Port could become a pioneering model for sustainable logistics in Eastern Indonesia. This research contributes empirically to the discourse on port sustainability by providing localized insights applicable to other regional ports.